Exploring Lecturers' Insights on Metacognitive Scaffolding in Writing Instruction - Anugrah Puspita Ayu Muhammad; Kisman Salija; Muhammad Basri; Waode Ade Sarasmita Uke (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This study investigates lecturers' perceptions of metacognitive scaffolding in writing instruction at Universitas Halu Oleo. Utilizing a qualitative exploratory case study design, data were collected through interviews with three lecturers from the Faculty of Teacher Training and Education. Thematic analysis revealed that while lecturers acknowledge the benefits of metacognitive scaffolding for developing independent writers, they encounter obstacles such as large class sizes, time constraints, and varied student engagement. The study aimed to provide insights for improving writing instruction practices and policy development. Lecturers discovered that metacognitive scaffolding is essential for helping students develop writing performances and engagement. The study’s findings align with literature emphasizing the importance of metacognitive strategies and structured feedback in writing instruction. The integration of technology and the positive impact of lecturers' personalities further support the effectiveness of metacognitive scaffolding in enhancing students' writing performance and engagement. Lecturers perceive the implementation of metacognitive scaffolding in writing courses as crucial for improving students' writing performance and fostering independent, reflective learning, although they acknowledge challenges such as students' difficulties with coherence and vocabulary and the distractions of technology.